'Islam in Pahang' named as the best original work - Muhammad Azli, Shukri (Penerbit UMP, 2013)
An original work titled, 'Islam in Pahang' by Centre For Modern Language & Humanity Science Centre (CMLHS) Dean Professor Dr. Abd. Jalil Borham was announced as the winning entry for Publication Prize (UMP Publisher - The Best Original Work) during the Quality and Innovation Day 2013 held at Bukit Gambang Resort, Kuantan.